Transcriptome profiling of the liver among the prenatal and postnatal stages in chickens. (3rd August 2019) - Xu, E; Zhang, Long; Yang, Hua; Shen, Lulu; Feng, Yanzhong; Ren, Minmin; Xiao, Yingping
ABSTRACT: The liver is an important organ that has pivotal functions in the synthesis of several vital proteins, the metabolism of various biologically useful materials, the detoxification of toxic substances, and immune defense. Most liver functions are not mature at a young age and many changes happen during postnatal liver development, which lead to differential functions of the liver at different developmental stages. However, the transcriptome details of what changes occur in the liver after birth and the molecular mechanisms for the regulation of the developmental process are not clearly known in chickens. Here, we used RNA-sequencing to analyze the transcriptome of chicken liver from the prenatal (at an embryonic day of 13) to the postnatal stages (at 5 wk and 42 wk of age). A total of approximately 161.17 Gb of raw data were obtained, with 4, 127 putative and 539 differentially expressed lncRNAs, and with 13, 949 putative and 6, 370 differentially expressed mRNAs. Coexpression of lncRNAs-mRNAs in hepatic transcriptome analysis showed that the liver plays important roles in providing energy for organisms through the mitochondrial respiratory chain in chickens, meanwhile, acting as a crucial part of antioxidant stress. The developmental transcriptome date revealed that antioxidant defenses are likely to act on chicken embryo development and that significant functional changes during postnatal liver development are associated with the liver maturation of chickens. These results provide a timeline for the functional transcriptome transition from the prenatal to adult stages in chickens and will be helpful to reveal the underlying molecular mechanisms of liver development.